(untitled) (Research, Society and Development, 2022)
The aim of this study was to evaluate the antimicrobial susceptibility of essential oil from Lippia sidoides Cham, against Aggregatibacter actinomycetecomitans ATCC 29522 and Porphyromonas gingivalis ATCC 0644. The antimicrobial activity of L.sidoides Cham oil extracted from leaves and flowers and the constituents thymol and carvacrol through Minimum Inhibitory Concentration (MIC) and minimal bactericidal determination (CBM) against periodontopathogens Aggregatibacter actinomycetemcomitans (ATCC), Porphyromonas gingivalis (ATCC ). Te results revealed that the MIC recorded was 44.23 to 39.3 mg/mL for thymol and 28.45 to 28.15 mg/mL for carvacrol. These concentrations were considered bactericidal when CBM was evaluated. All analyzed substances showed a synergistic effect in association with chlorhexidine. Thus, it can be concluded that Lippia sidoides Cham was effective in inhibiting the in vitro growth of periodontopathogenic bacteria, presenting, therefore, biotechnological potential for use in the field of dentistry.